2020
DOI: 10.1186/s12887-020-02242-2
|View full text |Cite
|
Sign up to set email alerts
|

“The right time is just after birth”: acceptability of point-of-care birth testing in Eswatini: qualitative results from infant caregivers, health care workers, and policymakers

Abstract: Background: Testing for HIV at birth has the potential to identify infants infected in utero, and allows for the possibility of beginning treatment immediately after birth; point of care (POC) testing allows rapid return of results and faster initiation on treatment for positive infants. Eswatini piloted birth testing in three public maternities for over 2 years. Methods: In order to assess the acceptability of POC birth testing in the pilot sites in Eswatini, interviews were held with caregivers of HIV-expose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“… 11 , 36 These findings were echoed by a study from Eswatini that showed POC testing delivered in a health facility reduced many of the costs and concerns related to travel time for caregivers who lived far from health facility EID services. 37 In our study, caregivers and HCWs alike both highlighted the compatibility and fit of the community POC model within the MOH EID program, which they perceived as offering faster EID testing, fewer barriers to testing access, and more timely availability of results and treatment for HIV-infected infants. However, some caregivers in our study raised concerns about the lack of privacy during community-based POC EID testing and reported anxiety about inadvertent disclosure of HIV status to neighbors or family members from testing in the community.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“… 11 , 36 These findings were echoed by a study from Eswatini that showed POC testing delivered in a health facility reduced many of the costs and concerns related to travel time for caregivers who lived far from health facility EID services. 37 In our study, caregivers and HCWs alike both highlighted the compatibility and fit of the community POC model within the MOH EID program, which they perceived as offering faster EID testing, fewer barriers to testing access, and more timely availability of results and treatment for HIV-infected infants. However, some caregivers in our study raised concerns about the lack of privacy during community-based POC EID testing and reported anxiety about inadvertent disclosure of HIV status to neighbors or family members from testing in the community.…”
Section: Discussionmentioning
confidence: 75%
“…In a study done at health facilities in Eswatini, HCWs associated increased wait times with frequent POC EID machine errors and high demand for testing services. 37 In our study, study staff and caregivers thought that community-based POC EID testing would reduce the need for retesting due to misplaced or lost samples in facilities, which they indicated was common with traditional DBS-based PCR testing. Concerns about retesting were not trivial, as they generally related to worries surrounding the need to collect additional blood, which were perceived by some participants to be harmful to the infant or young child.…”
Section: Discussionmentioning
confidence: 76%
“…Among them, we can highlight: the lack of communication between different stakeholders in the healthcare system hinder the adoption and scaling-up of POCT usage [ 38 , 39 ], the increase workload for HCP discouraging them to use new technologies [ 39 , 40 ], and the differentiated background among users (e.g. medical/non-medical or specialized/non-specialized) plus the absence of continuum training cause lack of confidence in the POCT and the results [ 41 , 42 ]. Nevertheless, common facilitators were identified, such as: HCP enthusiasm to obtain same-day results [ 43 ], reduce re-consultations [ 14 , 40 ] and save patient’ travel expenses [ 44 ], the test influence patient-HCP interaction [ 45 , 46 ], and the non-requirement of specialized skills to operate the devices [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Kenya and Eswatini found POC BT to be highly acceptable to infant caregivers, as the reduction in waiting time for test results greatly reduced anxiety and fear, although many families noted feeling concern about infant pain or fragility. POC BT was also found to be acceptable to health workers, although they also expressed concerns about capacity, workload, sustainability, and post-test engagement of patients in care ( 20,21 ). Following the introduction of POC BT in Zimbabwe, we carried out a qualitative study on the acceptability of POC BT among health workers and infant caregivers.…”
Section: Introductionmentioning
confidence: 99%